Multidrug resistant Enterohaemorrhagic Esherichia coli serogroups in the faeces of hunted wildlife, Abeokuta, Nigeria (2022)
Wildlife plays significant roles in the dissemination and zoonotic transmission of pathogens. The enterohaemorrhagic Escherichia coli (EHEC) are associated with complicated cases of food-borne illnesses. This study investigated the presence of EHEC serogroups (026, 045, 0103, 0145, 091, 0111, 0128, 0121 and 0157) in wildlife species: cane rats (Thryonomys swinderianus), royal antelope (Neotraguspygmaeus), African giant rats (Cricetomysgambianus) and \Naterbuck(Kobusellipsiprymnus). EHEC and non-EHEC isolates from these wildlife sources were tested for susceptibility to antimicrobial agents. Overall, 127 (83.0 %) out of 153 samples yielded E. coli. Nine (5.9%) samples were positive for EHEC belonging to three serogroups as follows: 026 (n = 2), 0111 (n = 2) and 0103 (n = 5). The EHEC isolates were from cane rats (n = 6) and royal antelope (n = 3) and possessed virulence-associated genes stx, (77.8%), stx2 (100.0%), eaeA (100.0%) and hlyA (100.0%). Overall, 127 £ coli isolates showed resistance to ampicillin (99.2%), ceftiofur (90.6%), tetracycline (90.0%), cephalexin (87.4%), cefotaxime (50.4%), streptomycin 42.5%, ceftazidime (41.7%), nalidixic acid (37.0%), ciprofloxacin (43.6%), amoxicillin/davulanic acid (32.3%), gentamicin (27.6%), sulphamethoxazole/ trimethoprim (25.2%), norfloxacin (17.3%) and chloramphenicol (11.0%). The role of wildlife in the dissemination and transmission of antimicrobial resistant and zoonotic bacteria should not be neglected for effective preventive and control strategies.